EXISTENTIALISM IN ARABIC LITERATURE: PHILOSOPHICAL FOUNDATIONS, MODELS, FIGURES, AND CRITICISM - Ulwiyah, Risadatul (Linguistik : Jurnal Bahasa dan Sastra, 2023)
This article discusses existentialism in Arabic literature. The purpose of this study is to describe the philosophical foundations that underlie existentialism, models or forms of existentialism, figures who apply existentialism in their literature works, critiques of existentialism. The method used in collecting data is the technique of looking at notes on reference sources in books related to existentialism. The results of the study show that the foundations philosophical of existentialism is that humans have the highest authority in governing themselves with responsible freedom. The models that appear in this exsistentialism are novels, dramas, poetry with themes of anxiety, sadness and others. Arab literary figures who apply this exsistentialism in their works include: 'Abd al-Rahman Badawi, Khalil al-Hawi, Abd al-Wahab al-Bayati, Taufiq al-Hakim. Later in its development, existentialism received some criticism because of its extreme ideas which were contrary to what was brought by Islam, that humans must believe in God and the values of intellectual heritage.